Aromatics extraction from pyrolytic sugars using ionic liquid to enhance sugar fermentability. (September 2016) - Li, Xiaohua; Luque-Moreno, Luis C.; Oudenhoven, Stijn R.G.; Rehmann, Lars; Kersten, Sascha R.A.; Schuur, Boelo
Graphical abstract: Ionic liquids showed promising separation properties for pyrolytic sugar streams with high selectivity of aromatics over sugars and produced sugar was hydrolyzed and then fermented to ethanol. Highlights: Aromatics were effectively extracted from pyrolytic sugars by P666, 14 [N(CN)2 ]. Sugars were not extracted at all. Regenerated IL exhibited similar aromatics extraction efficiency. Pure 40 g L −1 pyrolytic-glucose stream could directly be fermented. Abstract: Fermentative bioethanol production from pyrolytic sugars was improved via aromatics removal by liquid–liquid extraction. As solvents, the ionic liquid (IL) trihexyltetradecylphosphonium dicyanamide (P666, 14 [N(CN)2 ]) and ethyl acetate (EA) were compared. Two pyrolytic sugar solutions were created from acid-leached and untreated pinewood, with levoglucosan contents (most abundant sugar) of 29.0% and 8.3% (w/w), respectively. In a single stage extraction, 70% of the aromatics were effectively removed by P666, 14 [N(CN)2 ] and 50% by EA, while no levoglucosan was extracted. The IL was regenerated by vacuum evaporation (100 mbar) at 220 °C, followed by extraction of aromatics from fresh pyrolytic sugar solutions. Regenerated IL extracted aromatics with similar extraction efficiency as the fresh IL, and the purified sugar fraction from pretreated pinewood was hydrolyzed to glucose and fermented to ethanol, yielding 0.46 g ethanol/(g glucose), close to the theoretical maximum yield.